Gender Analysis of a Short Story’s Characters: An Analysis of The Gift of the Magi by O. Henry - Sella Anindita Latanggang; Siti Mahripah, S.Pd., M.App.Ling. (Jurnal Penelitian Humaniora, 2022)
This paper investigated the topic of gender in one of the most popular works written by O. Henry, the Gift of the Magi. The text was analyzed using Halliday’s Transitivity analysis of functional grammar (Matthiessen, C Halliday, 2014).The data of the text that being analyzed were types of the processes, participant roles, and types of circumstances in the clauses. The result showed that male character is more likely to use Material processes that are assumed to have more energy than those used by the female character.Keywords: short story, transitivity analysis, gender language characteristic